PENGARUH REKRUTMEN DAN PENEMPATAN TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) PEMATANGSIANTAR - Agus, Nurul Safika; Lie, Darwin; Efendi, Efendi; Julyanthry, Julyanthry (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The objective of this research was to test the influence of recruitment and placement to employee performance in a simultaneous and partial. The population used in this research are 23 employee. Research data were primary data and secondary data. Data were throught questionnaires, interviews, and documentaries. Analyzing method used was Qualitative Analysis and Analysis Quantitative. Quantitative Analysis proceed with application of SPSS version 21. The finding of this research and hypotesis test showed that recruitment and placement had significant influence to the employee performance partially and simultaneously.Â Keywords: Rekruitmen, Placement, and Employee Performance